Renormalization of Group Field Theories for Quantum Gravity: New Computations and Some Suggestions - Finocchiaro, Marco; Oriti, Daniele (Frontiers in Physics, 2021)
We discuss motivation and goals of renormalization analyses of group field theory models of simplicial 4d quantum gravity, and review briefly the status of this research area. We present some new computations of perturbative GFT (spin foam) amplitudes, concerning in particular the scaling behaviour of radiative corrections to N-point functions. Finally, we single out key open issues and suggest a number of research directions for further progress in this area.